Portraying refugees in British print media: the case of NATO airstrikes on Yugoslavia - Lakić, Igor (Círculo de Lingüística Aplicada a la Comunicación, 2018)
This paper is based on a critical discourse analysis (CDA) of three British dailies (the Guardian, the Independent and the Times) on NATO air strikes on Yugoslavia. The paper briefly introduces van Dijk’s notions of microstructures and macrostructures of newspaper articles and discusses some aspects of CDA (van Dijk, Fairclough), especially its approach of combining linguistic analysis with intertextual analysis. It then focuses on the issues of dominance and politics. The paper starts from the assumption that the concepts of dominance, power and politics are linked to the role of language that shapes or legitimates particular views, which is also the case in the corpus we analyzed. Politicians always use media in wartime to persuade citizens in a justness of war, leading consumers of news to uncritically accept that the ‘news’ presented to them is true. The paper offers examples from the three dailies and discusses them based on the theoretical approach taken. It briefly touches upon macrostructures and focuses on the elements on the micro level (verbs, nouns, noun phrases and adjectives) that are important for the interpretation of the analyzed articles